VARIETY OF LANGUAGES FOR SOCIAL MEDIA FOR THE DEVELOPMENT OF ANIMATION VEDIO BASED ON DIGITAL DICTIONARY - Aljamaliah, S. Nailul Muna; Kesha, Cut Nabilla; Darmadi, Deden Much (University of Kuningan, 2024)
The ease of communicating has an impact on the language used in social media, usually in influencer content on social media that can affect the practice of using Indonesian. Unknowingly, language content on social media affects language rules and new words are increasingly appearing. The formulation of the problem in this study is how is the variety of languages in social media for the preparation of animated video-based digital dictionaries? And what about the meaning of language in social media for compiling animated video-based digital dictionaries? This study aims to determine the variety of social media languages and find out the meaning of language in social media for the preparation of animated video-based digital dictionaries. This is to make it easier for readers to distinguish meaning and distinguish standard language varieties on social media. The research method used is descriptive. The data collection technique is collecting various languages through social media such as Facebook, Twitter, YouTube, and Tiktok. Data analysis techniques include data collection, making animated videos, presenting data, and drawing conclusions. The research steps include planning, implementing, and collecting reports. The results of this study are for the preparation of various languages of social media based on video animation. Based on these results will be explained in the form of qualitative descriptive.Keywords: variety of languages; social media; digital dictionary; animation video